A Survey on Addressing IoT Security Issues by Embedding Blockchain Technology Solutions: Review, Attacks, Current Trends, and Applications - Nathalie Tan Yhe Huan; Zuriati Ahmad Zukarnain (IEEE Access)
By 2025, the Internet of Things (IoT) infrastructure is projected to encompass over 75 billion devices, facilitated by the increasing proliferation of intelligent applications. The IoT ecosystem consists of sensors that function as data generators and applications that necessitate financial transactions to compensate the data producers. Security is a highly important concern. Typically, IoT gadgets are vulnerable to security breaches, and the advancement of industrial systems might introduce severe security weakness. The rapid evolution of IoT technologies and deployment scenarios makes the existing research challenging to keep pace with emerging threats and vulnerabilities. Employing blockchain technology makes it feasible to enhance security by maintaining payments in a ledger that is not just secure but also translucent, distributed, and immutable. This article provides an introductory overview of the IoT and subsequently delves into the many security threats and vulnerabilities arising within the IoT framework. This study provided an overview of the blockchain, focusing on its categorization and important properties. Moreover, this article examines the necessity of combining blockchain technology with the IoT, in addition to reviewing relevant literature and the studies conducted by other scholars. This article offers insight into the uses of blockchain on the Internet of Things (IoT).